A fifteen level modified active neutral point clamped multilevel converter for isolated power supply systems - Thomas Jacob, Jeby; D Kirubakaran, Dr. (International Journal of Engineering and Technology, 2019)
The application of multilevel level power converters in various fields of electrical industry gained momentum during the last decade. Hybrid multilevel converters (HMC) are emerging as an alternative to the conventional two stage inverter topology in high and medium power industrial sectors. Consistency in operation, quality of output power and litheness in enhancement are the vital factors contributed to the development of hybrid multilevel converters. The major challenge met by HMC’s are to attain a trade-off between the number of dc sources, switching devices and voltage levels. This paper presents the development of a modified active neutral point clamped fifteen level multi-level converter for isolated power supply electric systems. A Variable Frequency Overlapped Carrier (VFOC) modulation scheme is implemented for capacitor voltage balancing and switching loss reduction. Proposed system has been simulated under Matlab Simulink environment and a low power laboratory prototype is developed for endorsing the reliability and efficiency of the proposed converter.